Chemical analysis and antioxidant properties of orange‐tree (Citrus sinensis L.) biomass extracts obtained via different extraction techniques. (22nd February 2020) - Bruno, Maria R.; Russo, Daniela; Cetera, Paola; Faraone, Immacolata; Lo Giudice, Valentina; Milella, Luigi; Todaro, Luigi; Sinisgalli, Chiara; Fritsch, Clemént; Dumarçay, Stéphane; Gérardin, Philippe
Abstract: Orange orchards are typical Mediterranean crops and a major feature of the heritage of the Mediterranean basin, where they play an important environmental and economic role. Their high availability, low price, and potential industrial application make the development of new and valuable uses of the orange's biomass of high interest. This research was focused: (i) on recognition and mapping of orange cultivation in the Basilicata region; (ii) on the evaluation of the antioxidant capacity of extracts; (iii) on identification of extractives' traits. To achieve these objectives, the anti‐oxidative properties and chemical compounds of the extracts from orange orchard biomass were analyzed. Different extraction techniques were applied, including maceration, ultrasound‐assisted extraction, accelerated solvent extraction, and autoclaving. Results demonstrated the potential antioxidant activity of the bark and wood of orange‐tree biomass, which has not been investigated before. The relative antioxidant capacity index showed that bark extracts were more effective than wood ones, and accelerated solvent extraction was the most effective process for recovering antioxidants. Chemical characterization by liquid chromatography–mass spectrometry (LC–MS) showed the presence of different natural compounds, including caffeic acid, alkaloids, and flavonoids. The development of innovative applications that use biomass derivatives could lead to their possible use in the market as a commodity for the chemical or cosmetic industries, giving new added value to the current use of biomass from agricultural practices. Through multi‐criteria analysis it was possible to recognize the sustainability of these cropping models and their ecological function, using them for the preservation of environmental resources, environmental quality, and quality of life. © 2020 Society of Chemical Industry and John Wiley & Sons, Ltd